Strategi Efektif Pengelolaan Sarana dan Prasarana untuk Meningkatkan Mutu Pendidikan - Agustina, Anna; M. Fikri Haikal; Slamet Untung (IAIN Ambon, 2024)
The effective management of educational facilities and infrastructure is crucial for ensuring optimal educational quality. This study explores strategies to manage facilities and infrastructure, emphasizing the stages of planning, procurement, inventory management, maintenance, and disposal of facilities. These stages are aimed at ensuring that resources are effectively utilized to support the teaching and learning process. The research adopts a qualitative approach with library research, analyzing relevant literature on the management of educational facilities and its impact on quality improvement. The findings highlight that effective management practices must adhere to key principles such as effectiveness, efficiency, compliance with standards, and sustainability. By applying these principles, educational institutions can optimize resources, ensure regulatory compliance, and adapt to technological advancements and modern educational needs. Ultimately, a well-managed system of facilities and infrastructure contributes significantly to creating an innovative and sustainable educational environment that enhances learning outcomes and overall educational quality.